KESADARAN HUKUM MASYARAKAT DALAM BERLALU LINTAS DIKAITKAN DENGAN TINGGINYA ANGKA KECELAKAAN DI KEPOLISIAN SEKTOR TAMBANG BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
At the present time the motor vehicle is a necessity for every human being, a motor vehicle is any vehicle that is driven by mechanical equipment such as engines other than vehicles running on rails. In which security and traffic safety is a must for every motorist as stipulated in Law Number 22 Year 2009 regarding Traffic and Road Transportation. The purpose of this thesis are: First, to determine public awareness in traffic associated with the high number of accidents in the Police Sector Mine based. Second, to determine the constraints faced by the police in handling public legal awareness in traffic. Third, To know the efforts made by the police to address the low level of awareness of society in road traffic law.Keywords: Legal Awareness - Passes Cross – Accidents